The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/brainsci10080547
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Function Improvement in Mouse Model of Alzheimer’s Disease Following Transcranial Direct Current Stimulation

Abstract: Anodal transcranial direct current stimulation (tDCS) is a painless noninvasive method that reportedly improves cognitive function in Alzheimer’s disease (AD) by stimulating the brain. However, its underlying mechanism remains unclear. Thus, the present study investigates the cognitive effects in a 5xFAD AD mouse model using electrophysiological and pathological methods. We used male 5xFAD C57BL/6J and male C57BL/6J wild-type mice; the dementia model was confirmed through DNA sequencing. The verified AD and wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
(34 reference statements)
0
1
0
Order By: Relevance
“…It is an accepted notion that tDCS modulates brain activity partly by affecting synaptic functioning. Several studies showed that tDCS altered synaptic efficacy leading to long term potentiation or depression, depending on the direction of field polarity (Fritsch et al, 2010;Grassi et al, 2017;Kim et al, 2020;Kronberg et al, 2020Kronberg et al, , 2016Lafon et al, 2016;Podda et al, 2016;Yu et al, 2019). Most of these DCS studies utilized hippocampal slices.…”
Section: Resultsmentioning
confidence: 99%
“…It is an accepted notion that tDCS modulates brain activity partly by affecting synaptic functioning. Several studies showed that tDCS altered synaptic efficacy leading to long term potentiation or depression, depending on the direction of field polarity (Fritsch et al, 2010;Grassi et al, 2017;Kim et al, 2020;Kronberg et al, 2020Kronberg et al, , 2016Lafon et al, 2016;Podda et al, 2016;Yu et al, 2019). Most of these DCS studies utilized hippocampal slices.…”
Section: Resultsmentioning
confidence: 99%